Digital Technology and the Interactive Television - Souza, Ozéias Teixeira de (2008)
In this article it is analyzed the impact that the digital technology process causes in the way that television participates of the social life in Brazil. Trying a non-hermeneutic approach, it is proposed to think this new role of television, from the materiality existing on this media that can bring more interactivity and conducts the changes over people behavior. In our opinion, we realize that materiality can support the transposition of the nowadays analogical interaction form the televiewer-television model to a user-machine model in the digital television.